Case Report: Chinese female patients with a heterozygous pathogenic RPS6KA3 gene variant c.898C>T and distal 22q11.2 microdeletion - Cong, Yan; Jin, Hongxing; Wu, Ke; Wang, Hao; Wang, Dong (Frontiers in Genetics, 2022)
Background: Coffin–Lowry syndrome (CLS) [OMIM#303600] is a rare X-linked dominant syndrome. CLS is caused by highly heterogeneous loss-of-function mutations in the RPS6KA3 gene (OMIM*300,075). CLS is characterized by intellectual disability (ID), short stature, tapered fingers, characteristic facial features, and progressive skeletal changes. Distal 22q11.2 microdeletion syndrome (OMIM#611867) is an autosomal dominant and recurrent genomic disorder. It mainly includes three types [distal type I (D–E/F), type II (E–F), and type III (F–G)] and exhibits variable clinical phenotypes (mild, moderate, or even normal): preterm birth, pre- and/or postnatal growth restriction, development delay, ID, behavioral problems, cardiovascular defects, skeletal anomalies, and dysmorphic facial features. We investigated the genetic etiology of a Chinese pedigree with ID, short stature, digit abnormalities, facial dysmorphism, and menstrual disorder. A heterozygous RPS6KA3 gene variant c.898C>T (p.R300X) was identified in this familial case. Two female CLS patients with distal 22q11.2 microdeletion presented with more severe clinical phenotypes. We provided clinical characteristics of these Chinese female CLS patients. Case presentation: We described a Chinese family with three affected females (the mother, the elder sister, and the proband). The mother and the elder sister had more severe clinical phenotypes (moderate facial dysmorphism, more severe cognitive impairment, and shorter stature). The common characteristic phenotypes are ID, short stature, facial dysmorphism, irregular menstruation, and cardiovascular disorders. Peripheral blood samples were collected from the pedigree. Whole-exome sequencing (WES) identified a heterozygous nonsense RPS6KA3 gene variant c.898C>T (p.R300X). It was verified by Sanger sequencing. Copy number variation sequencing (CNV-seq) showed that both the mother and the elder sister carried a CNVseq [hg19] del (22) (q11.22-q11.23) (22997582–23637176)×0.5. RNA from peripheral blood samples was used for measuring the relative quantification of mRNA (expressed by exon 14 of RPS6KA3). The levels of mRNA relative expressions were significantly lower in the mother’s and the elder sister’s blood samples. The levels of mRNA relative expressions were significantly higher in the proband’s blood sample. X-chromosome inactivation (XCI) studies demonstrated that the proband showed extremely skewed XCI, and the XCI pattern of the elder sister was random. Conclusion: Herein, we reported three Chinese female patients with a heterozygous nonsense RPS6KA3 gene variant c.898C>T. Further genetic studies were performed. To our knowledge, Chinese patients with this variant have not been previously reported in the literature. The three female patients presented with variable degrees of severity. The clinical characteristics of these Chinese female CLS patients could expand the phenotypic spectrum of CLS. We helped physicians to understand the genotype–phenotype correlation further.